Caracterização do contorno do movimento de língua de adolescentes e adultos com erros residuais de fala - Uberti, Letícia Bitencourt (2019)
During speech acquisition, many children may have Speech Sound Disorders, which may or may not be treated with speech therapy. When, after age nine, these speech disorders persist, they are called Residual Speech Errors. Residual Speech Errors are still poorly studied in the national literature and studies relating this disorder to instrumental assessments are even scarcer, although there are studies showing that the negative impact of these changes on adulthood can be significant. Studies report that in this population the most found alterations are in the production of fricative and liquid phonemes, due to their complexity of articulation. Therefore, this study was developed with the purpose of characterizing the fricative and liquid mean tongue contours in adolescents and adults with typical speech production and Residual Speech Errors, since both sound classes are the most common present alterations in the population older than 12 years. Through this study, we seek to emphasize the importance of evaluating speech with instruments that allow the clinician to identify each level of production, with the purpose of better visualization of the pathology. Speech, speech, hearing and hearing assessments were performed with subjects aged 12 to 44 years and 11 months, with and without complaints of speech disorders. In addition, the ultrasonography assessment of tongue movements was performed with the purpose of instrumentally characterizing the speech production of the research participants and allowed the differentiation of the average contours of the tongue in the different groups. The results allowed us to conclude that in the assessment of orofacial motricity and ultrasonography, the group with residual speech errors presented more difficulty in tongue mobility, characterizing an immaturity of the development of the motor tongue control. The fricative and liquid phonemes presented differences in the mean tongue contours when comparing the production of these phonemes in both groups. In addition, the subjects with alterations in liquids had more production variability in the characterization of the mean tongue contours. The evaluation of the speech of the adult public is very important since a presence of alteration can negatively influence several factors in the life of these subjects.